2021
DOI: 10.1111/imj.14971
|View full text |Cite
|
Sign up to set email alerts
|

Screening for diabetic retinopathy and reduced vision among Indigenous Australians in Top End primary care health services: a TEAMSnet sub‐study

Abstract: Background Diabetic retinopathy (DR) prevalence is higher in Indigenous Australians than in other Australians and is a major cause of vision loss. Consequently, timely screening and treatment is paramount, and annual eye screening is recommended for Indigenous Australians. Aims To assess the prevalence of DR, reduced vision and DR treatment coverage among Indigenous Australian adults with diabetes attending Top End indigenous primary care health services. Methods A cross‐sectional DR screening study conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The review identified 42 articles that reported on the incidence and prevalence of various eye diseases amongst the Indigenous population, including keratitis, visual impairment, vision loss, cataract, glaucoma, choroidal nevi, eye trauma, trachoma and diabetic retinopathy [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] ( Table 2 ). Irrespective of the study design, these studies collectively demonstrated that the prevalence of vision impairment and eye diseases in Aboriginal and Torres Strait Islanders (respectfully referred to as Indigenous Australians) is consistently higher compared to non-Indigenous Australians.…”
Section: Resultsmentioning
confidence: 99%
“…The review identified 42 articles that reported on the incidence and prevalence of various eye diseases amongst the Indigenous population, including keratitis, visual impairment, vision loss, cataract, glaucoma, choroidal nevi, eye trauma, trachoma and diabetic retinopathy [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] ( Table 2 ). Irrespective of the study design, these studies collectively demonstrated that the prevalence of vision impairment and eye diseases in Aboriginal and Torres Strait Islanders (respectfully referred to as Indigenous Australians) is consistently higher compared to non-Indigenous Australians.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 15 studies enrolling 8219 diabetic participants were included in our systematic review and metaanalysis. 7,8,[24][25][26][27][28][29][30][31][32][33][34][35][36]…”
Section: Study Selectionmentioning
confidence: 99%